Treasure hunt: the quest for knowledge by hotel employees in Dubai, UAE. Issue 2 (3rd April 2023) - Newnham, Michael P.; Dutt, Christopher S.
Abstract: Sharing and exchanging knowledge among workers in organizations has received considerable attention in the literature, whereas knowledge seeking attitudes and behavior are less reported. This paper presents findings from a qualitative study of knowledge seeking by hotel employees in Dubai, UAE. Distinctive characteristics of hotel workforces in Dubai are identified. Employees emphasized proactive knowledge seeking, rather than knowledge sharing. These findings highlight the importance of providing organizational support for pull learning approaches to employees' knowledge acquisition, through technology-enabled microlearning practices. In this way, organizations are likely to benefit from greater employee satisfaction, retention, competence and productivity.